3(2x-14)+x=15-(-9x-5)

Simple and best practice solution for 3(2x-14)+x=15-(-9x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-14)+x=15-(-9x-5) equation:


Simplifying
3(2x + -14) + x = 15 + -1(-9x + -5)

Reorder the terms:
3(-14 + 2x) + x = 15 + -1(-9x + -5)
(-14 * 3 + 2x * 3) + x = 15 + -1(-9x + -5)
(-42 + 6x) + x = 15 + -1(-9x + -5)

Combine like terms: 6x + x = 7x
-42 + 7x = 15 + -1(-9x + -5)

Reorder the terms:
-42 + 7x = 15 + -1(-5 + -9x)
-42 + 7x = 15 + (-5 * -1 + -9x * -1)
-42 + 7x = 15 + (5 + 9x)

Combine like terms: 15 + 5 = 20
-42 + 7x = 20 + 9x

Solving
-42 + 7x = 20 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-42 + 7x + -9x = 20 + 9x + -9x

Combine like terms: 7x + -9x = -2x
-42 + -2x = 20 + 9x + -9x

Combine like terms: 9x + -9x = 0
-42 + -2x = 20 + 0
-42 + -2x = 20

Add '42' to each side of the equation.
-42 + 42 + -2x = 20 + 42

Combine like terms: -42 + 42 = 0
0 + -2x = 20 + 42
-2x = 20 + 42

Combine like terms: 20 + 42 = 62
-2x = 62

Divide each side by '-2'.
x = -31

Simplifying
x = -31

See similar equations:

| -4x+7x-6x=0 | | 4x+2(3x-5)=-60 | | 8x-1(6x-4)=10 | | n^2+10n+14=5 | | 10x-5=2x+6 | | 4x-118+3x=85 | | 5x+33=3x-31 | | 21n=-147 | | 5w-10=30 | | 69-5x=31x+17 | | 8x^3-16x^2-x+2= | | 7y-3=12y+4 | | 23*-12=-33 | | n^2-4n-6=-2 | | -74=-7x+3(-x+2) | | 26+x=12+x+23-(14+x) | | 26+x=12+x+23-14+x | | 2x-26+x=25 | | n^2+6n+22=2 | | 26+x=12+x+23 | | 2y=6x-2 | | 8(2x+9)=10x+2(3x-4) | | 6(8-2r)= | | -t^3+t^2+2t=0 | | -1(x+4)=5 | | 11(x+10)=132 | | -19-11x+12x=5 | | 5x+6(x-3)=42 | | 33=(3x-28)+(3x-30)+x | | 16=5a-9 | | 4(x+3)=6(3-x) | | 6x-24-4x=6 |

Equations solver categories